2008
DOI: 10.1007/s11356-008-0050-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resin and fatty acid concentration levels by online sample enrichment followed by atmospheric pressure chemical ionization-mass spectrometry (APCI-MS)

Abstract: Compared to the conventional methods used for this purpose, the main benefits of the method are rapidity of measurement, simplicity of use, and absence of the need for multistage sample treatments (short analysis time). For this reason, this online method is more suitable for the control of papermaking by analyzing the concentration levels of interfering substances (i.e., selected resin and fatty acids) than an offline analysis detailing all the individual extractives-based compounds in process streams. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…These results showed that the sampling location of the process water plays an important role when using individual resin acids as a marker for total resin content. Also, online sample enrichment using the APCI-MS technique without multistage sample pretreatment (shorter analysis time compared to traditional GC-FID analysis) was reported for the rapid analysis of certain common fatty and resin acids (Valto et al 2007(Valto et al , 2008(Valto et al , 2009). In addition, Monte et al (2004) developed a procedure in which destabilization of DCS with cationic polymer addition, deposit collection, and quantification with image analysis were used to predict the tendency of the material to form deposits.…”
Section: Applications Of the Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results showed that the sampling location of the process water plays an important role when using individual resin acids as a marker for total resin content. Also, online sample enrichment using the APCI-MS technique without multistage sample pretreatment (shorter analysis time compared to traditional GC-FID analysis) was reported for the rapid analysis of certain common fatty and resin acids (Valto et al 2007(Valto et al , 2008(Valto et al , 2009). In addition, Monte et al (2004) developed a procedure in which destabilization of DCS with cationic polymer addition, deposit collection, and quantification with image analysis were used to predict the tendency of the material to form deposits.…”
Section: Applications Of the Methodsmentioning
confidence: 99%
“…It also enabled the simultaneous separation and determination of the monitored ions, and a good correlation was obtained between changes in process conditions and ion concentrations. Also, the use of a centrifugal pump and a ceramic filter connected to the APCI-MS system with time-controlled column switching valves for the analysis of concentration levels of fatty and resin acids in papermaking process waters has been reported (Valto et al 2009). In addition, Chai et al (2002) have developed an attenuated total reflection (ATR) UV-sensor, which could replace the online automatic titration systems by online monitoring of sulfide, hydroxide, and carbonate ions in kraft pulp white liquors.…”
Section: Online Analysis and Process Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that mechanical pulping processes result in the release of substantial amounts of DCS even when pure, neutral water is used as the medium (Thornton et al 1994a;Cesek and Milichovsky 1996;Örså et al1997;Valto et al 2009). Greater amounts of such materials tend to be released when pulping is carried out under alkaline pH conditions He et al 2004;Maximova et al 2004;Mou and Qin 2006;Lehmonen et al 2009).…”
Section: Wood As a Main Source Of Charge Demandmentioning
confidence: 99%
“…In our previous studies [20][21][22], the emphasis was put on the development of a rapid screening method for selected fatty and resin acids in papermaking process waters using an online sample enrichment technique without a traditional HPLC column separation for possible online use in a paper machine environment. As a continuation of these investigations, this paper concentrates on the development of a faster offline laboratory method for these acids with a standard injection, a HPLC column separation, and a thorough method validation process with internal standard quantitation.…”
Section: Introductionmentioning
confidence: 99%